Global justice and environmental governance: an analysis of the Paris Agreement - Santos,Marcelo (2017)
Abstract Based on the major normative political theory contributions on global climate justice, the present paper analyzes the new international agreement on climate change, adopted at COP 21 in Paris (2015). Therefore, a literary review of the extensive normative theoretical discussion about global climate justice is made, with special attention to the two approaches that have permeated multilateral political negotiations - historical responsibility and equal per capita emissions. From this normative discussion, this paper recalls the global climate change negotiation process, focusing on the Kyoto Protocol. Next, the analysis emphasizes on the Paris Agreement in an effort to evaluate the normative questions on justice and equity within the environmental governance regime. Finally, the set of conclusions indicates that, although the flexibility of the Agreement has encompassed some dimensions of responsibility, necessity and ability to bear the costs, the most complex dimensions of justice and equity has not been completely solved, which may hinder the operation of environmental governance in a near future.